Enhancing IoT in education: a comprehensive analysis of CS110 students’ perceptions towards Do-It-Yourself (DIY) Workshops at UiTM Sarawak Branch / Lee Yee Ann ... [et al.] - Lee, Yee Ann; Abdul Talip, Abdul Hadi; Bohari, Zubaidah; Che Md Nor, Rumaizah (UiTM Cawangan Perlis, 2024)
The Internet of Things (IoT) revolutionizes by connecting everyday things to the Internet. Its growing use in diverse sectors has spurred innovative teaching methods and tools in education. Recently, a new topic called “Basic IoT” has been added to the Digital Electronics course offered in the Diploma in Computer Science (CS110) at UiTM. Before the topic was introduced, the students rarely worked directly with hardware components and knew little about IoT. Conventional teaching methods may fall short of providing students with hands-on experience. Therefore, five (5) DIY workshop sessions were conducted to expose the students to IoT. This research aims to determine the level of students' perceptions towards the DIY IoT workshop, evaluate the difficulty level for all modules throughout the DIY IoT workshop, and assess the effectiveness of DIY workshops in learning IoT. There were 21 students who participated in the workshop, where the students were introduced to the fundamentals of the Internet of Things, the ESP32 microcontroller and the installation of Arduino IDE software, the method of lighting LEDs using ESP32, the method of connecting ESP32 to a Wi-Fi network, as well as the method of reading data from sensors and sending data to Google Sheets. Online questionnaires were disseminated at the end of the workshop, and a short interview was conducted to gain the students’ perceptions of the workshop. Data analysis was conducted in three primary phases: descriptive statistics, mean scores, and t-tests using the Statistical Package for the Social Sciences (SPSS). This study's outcome indicates that students have positive perceptions towards the DIY workshop in learning IoT (t = -9.34, p-value (0.000) < 0.05), contributing to SDG 4 (Quality Education). Hence, it offers invaluable insights into the role of experiential learning in IoT education and provides actionable recommendations for optimizing the workshop.